Responsibility of Notary in The Making of Agreement Which Impacted to The Credit Loss in Bank Mega Branch of Kudus - Totok Sujatmiko; Malik AL-Ghazali; Munsharif Abdul Chalim (Jurnal Akta, 2018)
Notaries are defenders of truth and justice so that law enforcement officials must carry out in good faith and sincerity, so that the legal profession is an honorable and noble profession (officium nobile). The number of notaries make increasingly tight competition between the notary and the notary sometimes make less cautious in their profession. The paper concludes that the Notary responsible for what was witnessed, which is seen, heard and done by notaries as public officials in the run position. Notaries are not responsible if any proofs and documents that are not true of the applicant.Keywords: Notaries; Agreements; Identity.